Characterization and novel analyses of acute stress response patterns in a population-based cohort of young adults: influence of gender, smoking, and BMI. (3rd March 2016) - Herbison, Carly E.; Henley, David; Marsh, Julie; Atkinson, Helen; Newnham, John P.; Matthews, Stephen G.; Lye, Stephen J.; Pennell, Craig E.
Abstract: Dysregulation of the biological stress response system has been implicated in the development of psychological, metabolic, and cardiovascular disease. Whilst changes in stress response are often quantified as an increase or decrease in cortisol levels, three different patterns of stress response have been reported in the literature for the Trier Social Stress Test (TSST) (reactive-responders (RR), anticipatory-responders (AR) and non-responders (NR)). However, these have never been systematically analyzed in a large population-based cohort. The aims of this study were to examine factors that contribute to TSST variation (gender, oral contraceptive use, menstrual cycle phase, smoking, and BMI) using traditional methods and novel analyses of stress response patterns. We analyzed the acute stress response of 798, 18-year-old participants from a community-based cohort using the TSST. Plasma adrenocorticotrophic hormone, plasma cortisol, and salivary cortisol levels were quantified. RR, AR, and NR patterns comprised 56.6%, 26.2%, and 17.2% of the cohort, respectively. Smokers were more likely to be NR than (RR or AR; adjusted, p < 0.05). Overweight and obese subjects were less likely to be NR than the other patterns (adjusted, p < 0.05). Males were more likely to be RR than NR (adjusted, p = 0.05). In addition, we present a novel AUC measure (AUCR ), for use when the TSST baseline concentration is higher than later time points. These results show that in a young adult cohort, stress-response patterns, in addition to other parameters vary with gender, smoking, and BMI. The distribution of these patterns has the potential to vary with adult health and disease and may represent a biomarker for future investigation.